Isolation, characterization and molecular identification of seed-borne bacterial pathogens of rice in Bangladesh (Annals of Bangladesh Agriculture, 2025)
Rice is attacked by many pathogens including seed-borne bacteria resulting considerable amount of yield loss. The current experiment was conducted to isolate, characterize and molecularly identify the seed-borne bacteria from the infected rice grain. A total of 60bacterial isolates was isolated from the 60 rice samples collected from Gazipur, Tangail and Mymensingh district during 2018-19 and 2019-20 rice growing seasons (Aman and Boro). Out of 60 bacterial isolates from rice, 20 isolates namely B1, B2, B8, B9, B10, B13, B14, K3,K8, T4, T5, T6, T10, T14, T16, M3, M5, M9, M10, and M13 produced grain rot symptoms. Among 20 isolates, 9 isolates namely B9, B10, B13, K8, T5, T16, M3, M10 and M13 produced blight symptoms along with grain rot. They showed yellow in colony colour and positive in KOH solubility test, catalase test, growth at 36 °C, gelatin liquefaction test and mucoid growth on Yeast extract-dextrose-CaCO3 (YDC) whereas negative in oxidative test, urease production, and fermentation of glucose tests. Based on results, nine isolates were identified as Xanthomonas oryzae. Rest 11 isolates namely B1, B2, B8, B14, K3, T4, T6, T10, T14, M5 and M9 showed white or greyish white in culture condition, positive in KOH solubility test, catalase test, growth at 36 °C, urease production and gelatin liquefaction test, but negative in oxidative test, fermentation of glucose and mucoid growth on YDC tests, identified as Burkholderia glumae. To verify the results of physiological and biochemical tests, representative five yellow and five white or grayish white colony colour isolates then characterized by 16S rDNA sequencing. Five yellow colony colour isolates confirmed as X. oryzae and the other five white colony coloured as B. glumae. Therefore, this finding will help to explore the effective management against the seed-borne bacterial pathogens of rice.Ann. Bangladesh Agric. 28(1): 49-60